Unlocking Corporate Core Values : Are They Lost in the Shuffle? - Zaini, Embong; Mohd Waliuddin, Mohd Razali; Kamarul Baraini, Keliwon; Romlah, Jaffar (2024)
Corporate core values serve as the guiding principles that shape an organization's culture, operations, and interactions. These values articulate the fundamental beliefs and ideals that drive decision-making and behavior within the company. This aspect, however, seems to be forgotten in research related to corporate behaviour. Since decisions such as voluntary disclosure, corporate social responsibility (CSR) and sustainable operation are shaped by surroundings and culture, there is possibility that decision regarding these is influenced by corporate core values. The objective of this paper is to explore the corporate core values of companies listed on Bursa Malaysia. This study uses measurement of core values as proposed by Bourne et al. (2019). There are four categories that emphasize (1) efficiency, (2) character, (3) interpersonality and (4) community. Keywords from core value statement included in annual report are collected. The keyword is then categorized into the four categories as suggested by Bourne et al. and the highest score among the four categories will indicate the emphasis of the company. It is pertinent to comprehend the value or inclination of companies in order to further understand corporate behaviour. Hence, we anticipate that the core values of companies portray its business conducts for example, companies in the consumer industry have values that emphasis on interpersonality, etc. The findings of this study can give insight into studies related to corporate behaviour in the future.